Crystallographic tomography and molecular modelling of structured organic polycrystalline powders. Issue 13 (5th March 2021) - Gajjar, Parmesh; Nguyen, Thai T. H.; Sun, Jun; Styliari, Ioanna D.; Bale, Hrishikesh; McDonald, Samuel A.; Burnett, Timothy L.; Tordoff, Benjamin; Lauridsen, Erik; Hammond, Robert B.; Murnane, Darragh; Withers, Philip J.; et al.
Abstract : Novel combination of crystallographic tomography and molecular modelling is used to examine the powder packing behaviour and crystal interactions for an organic polycrystalline powder bed. Abstract : A fundamental understanding of the behaviour of polycrystalline materials, including pharmaceuticals, is vital for control of their physicochemical and crystalline properties, which in turn has the potential to improve drug product development for example. In this work, attenuation X-ray computed tomography (CT) and diffraction contrast tomography (DCT) are combined with molecular modelling to understand the powder packing behaviour and crystal interactions of the organic cubic compound hexamine (hexamethylenetetramine). It is the first application of DCT to polycrystalline organic materials. The crystal morphology is predicted through synthonic modelling, with fully 3D-resolved confirmation of the crystallography of the external {110} facets, edges and corner directions by DCT. Analysis of the powder-bed reveals agglomerate structures and orientational texture, with its chemical origins energetically predicted to be face-to-face in accordance with the experimental data. Finally, measurements of crystal & crystallite interactions provide evidence for different mechanisms of powder bed agglomeration.